Spectrum of Thrombotic Complications in Fatal Cases of COVID-19: Focus on Pulmonary Artery Thrombosis In Situ - Anastasiya S. Babkina; Mikhail Y. Yadgarov; Alexey V. Volkov; Artem N. Kuzovlev; Andrey V. Grechko; Arkady M. Golubev (Viruses, 2023)
COVID-19-related thrombosis affects the venous and arterial systems. Data from 156 autopsies of COVID-19 patients were retrospectively analyzed to investigate the pattern of thrombotic complications and factors associated with pulmonary artery thrombosis and thromboembolism. Thrombotic complications were observed in a significant proportion (n = 68, 44%), with pulmonary artery thrombosis the most frequently identified thrombotic event (42, 27%). Multivariate analysis revealed that the length of hospital stay (OR 1.1, p = 0.004), neutrophil infiltration in the alveolar spaces (OR 3.6, p = 0.002), and the absence of hyaline membranes (OR 0.1, p = 0.01) were associated with thrombotic complications. Neutrophil infiltration in the alveolar spaces (OR 8, p < 0.001) and the absence of hyaline membranes (OR 0.1, p = 0.003) were also independent predictors of pulmonary artery thrombosis. The association of pulmonary artery thrombosis with an absence of hyaline membranes suggests it occurs later in the course of COVID-19 infection. As neutrophil infiltration in the alveolar spaces may indicate bacterial infection, our studies suggest the consideration of bacterial infections in these critically ill patients.